2018
DOI: 10.1088/1361-6668/aad786
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting flux jumps for pulsed field magnetisation

Abstract: Magnetisation is one of the main barriers to practical use of bulk superconductors as high field magnets. Recently several authors have reported a flux jump effect that allows penetration of magnetic flux into a bulk superconductor during pulsed field magnetisation (PFM) at lower fields than that would be predicted on the basis of the Bean model. We have systematically investigated macroscopic flux jumps in single grain GdBa 2 Cu 3 O 7−δ -Ag (GdBCO-Ag) bulk superconductors with diameters of up to 30 mm when su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 40 publications
(51 reference statements)
5
47
0
Order By: Relevance
“…Here, the applied field, at which the Bt value begins to increase, is defined as the rise field, Br. The Bt value for S-sp(65 K) increases from Br = 3.06 T by the flux jump and the highest Bt value of 2.79 T was achieved at Bex = 3.76 T. The Bt value for S-sp(25 K) increased from Br = 4.17 T and a highest Bt of 3.96 T was achieved at Bex1 = 5.43 T. These rapid increases in Bt above Br result from flux jumps [11], [12] (or so-called giant flux leaps (GFLs) in other works [13]), which are a characteristic behavior when using the split-type coil. The rise field, Br, increased and the trapped field, Bt, was usually enhanced when lowering the operating temperature during single-PFM [14].…”
Section: Fig 3(a)mentioning
confidence: 91%
“…Here, the applied field, at which the Bt value begins to increase, is defined as the rise field, Br. The Bt value for S-sp(65 K) increases from Br = 3.06 T by the flux jump and the highest Bt value of 2.79 T was achieved at Bex = 3.76 T. The Bt value for S-sp(25 K) increased from Br = 4.17 T and a highest Bt of 3.96 T was achieved at Bex1 = 5.43 T. These rapid increases in Bt above Br result from flux jumps [11], [12] (or so-called giant flux leaps (GFLs) in other works [13]), which are a characteristic behavior when using the split-type coil. The rise field, Br, increased and the trapped field, Bt, was usually enhanced when lowering the operating temperature during single-PFM [14].…”
Section: Fig 3(a)mentioning
confidence: 91%
“…An avalanche-like flux jump occurs when the reduction in shielding ability exceeds the increment of Ba, and terminates when a critical state is re-established at the field penetration front. This indicates that a flux jump is prone to occur in a strong pinning scenario.In this paper, we report the PFM of a relatively larger GdBCO-Ag bulk sample than has been achieved previously [27] and an optimised magnetization strategy with a two-step multi-pulse process to routinely achieve a trapped field of 4.8 T.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate that a flux jump is an essential condition for obtaining such high trapped fields. We have simulated flux jumps numerically during the PFM process [26] and have extended the classical criterion for a flux jump to occur [27]. Exploiting this phenomenon, we obtained BT of 4.1 T measured at the surface and 5.3 T measured in-between a stack of two GdBCO-Ag samples of diameter 30 mm.…”
Section: Introductionmentioning
confidence: 99%
“…TMI is usually considered unfavorable for the application of SC thin films, which degrades the current carrying capacity due to the suppression of superconductivity in the hotspot area [ 9 ], introduces electromagnetic noises to SC devices during sudden entry or exit of vortices [ 10 ], and induces thermal strain or even damage to the material [ 11 , 12 ] due to the sharp temperature rises at hotspots. On the other hand, it was reported that TMI can be utilized to design flux injectors [ 13 ] or to magnetize bulk superconductors [ 14 ]. Experimental observations [ 15 , 16 ] and numerical simulations based on the cellular automaton [ 17 ] show that the distribution of vortex avalanche sizes, the duration and temporal power spectra follow power laws and demonstrate finite-size scaling which are indications of self-organized criticality (SOC) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%